The green lacewing genus Anachrysa Hölzel, 1973 stat. nov. (Neuroptera: Chrysopidae) from China, with description of two new species - Ma, Yunlong; Liu, Xingyue (Zootaxa, 2021)
A taxonomic study of the green lacewing genus Anachrysa Hölzel, 1973 from China is presented. Five species of Anachrysa are recorded from China. Two new species, Anachrysa lifashengi sp. nov. and Anachrysa luna sp. nov., which are described in this study, and three new combinations, i.e. Anachrysa holzeli (Wang & Yang, 1992) comb. nov., Anachrysa xiangana (Wang & Yang, 1992) comb. nov. and Anachrysa trigonia (Yang & Wang, 2005) comb. nov. are proposed. A key to species of Anachrysa from China is also provided.